Peculiarities Of Parallel Construction and Chiasmus In English And Uzbek Poetry - Karimova Shakhnozakhon Karimovna (Researchparks Publishing, 2024)
This study explores the use of parallel construction and chiasmus in English and Uzbek poetry, examining how these rhetorical devices enhance rhythm, meaning, and aesthetic quality. A comparative analysis highlights distinct cultural influences and linguistic structures that shape their application in each poetic tradition. Findings reveal that while parallelism is commonly used in both traditions for emphasis and symmetry, chiasmus serves unique functions, reflecting contrasting values and linguistic characteristics. These results contribute to a deeper understanding of how culture and language influence poetic form